Performance of irrigation: an assessment at different scales in Ethiopia - Awulachew, Seleshi Bekele; Ayana, M. (Cambridge University Press, 2011)
Ethiopia has an irrigation potential of 5.3 million ha (Mha) of which 3.7 Mha can be developed using surface water sources, and 1.6 Mha using groundwater and rainwater management. Irrigation contributes to rapid transformation of agriculture as present-day agriculture is dominated by rainfed single crops. The current irrigation development in Ethiopia is about 0.7 Mha, and the performance of the existing schemes is not well understood. As the country is planning to expand irrigated agriculture in the next five years, it will be useful to review existing performance and to identify areas for interventions that help revitalize underperforming systems. In this paper, we have investigated the performances of irrigation at three levels: (a) national level for broad performance, (b) regional level for small-scale irrigation and (c) scheme level for large-scale irrigation. National level indicators measure (i) the relative proportion of operating schemes, (ii) ratio of actually cultivated area to planned command area and (iii) relative number of benefited to targeted number of households. The result shows that 86.5% of schemes are operating, 74.1% of command area is under cultivation and only 46.8% of the planned beneficiaries have benefited fromimplemented irrigation. For regional level irrigation performances, the regions of Southern Nations and Nationalities and Oromia Regions were investigated. We used technological (structural) and management factors as measures of performances. Sixty-four underperforming schemes were sampled from the two regions to analyse the causes. About 30 parameters were identified as causes of underperformance. Watershed degradation related problems that are causing erosion and sedimentation of water control and conveyance structures are found to be the major cause for structural failures, while lack of sustainable funding, extension of agronomic practice, and post harvest technologies are identified as the top management-related problems. For evaluating performances of large-scale schemes, we used irrigation water delivery performance and output performance indicators applied to six large-scale schemes. Scheme level performance indicators results showed that all of the schemes considered have supplied adequate to excess amounts of water during the period. The Wonji scheme that uses pump diversion showed higher water use efficiency than other schemes that are using simple gravity diversion types. In this case it might be the running costs of pumps that have encouraged efficient management of water. In terms of output performance, sugarcane based irrigation schemes are superior and up to ten times that of banana, cotton, and maize or tobacco production. The results of these assessments are useful for decision-makers and disclosed the low performance of the existing irrigation schemes. They also indicated the need to revitalize existing schemes to improve performance in parallel to the implementation of new projects. The paper also provided new indicators of evaluation of performance with respect to national level, structural and management related performance.